Catching Dreams: Applying Gestalt Dream Work to Canadian Aboriginal Peoples - Elliott, Nicole (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
Gestalt therapy is similar to an Aboriginal worldview in that they both involve a holistic approach and focus on health and wellness strategies. The Aboriginal worldview is best portrayed as holistic in nature, where the circle of wellness symbolizes unity, wholeness, completeness, and balance. Dream work is a therapeutic technique utilized in Gestalt therapy that could be very useful for Aboriginal peoples given their spiritual and narrative way of being. This article demonstrates the cultural acceptability for utilization of dream work in Gestalt with Aboriginal clients. Furthermore, it discusses both strengths and limitations of this modality of therapy. Implications for use are also discussed.